Perancangan Sistem Pengendalian Drone Autonomous Quadcopter Dengan Smartphone Berbasis Android - Muhammad Adi Saputra; Nur Alif Mardiyah; Muhammad Nasar (Universitas Muhammadiyah Malang, 2021)
An Unmanned Aerial Vehicle (UAV) is an unmanned aircraft that can fly autonomously. Autonomous system in a drone quadcopter can minimize user control. An autonomous mode enables the drone to operate automatically based on the previously created setting, although the remote is off. One type of UAV that is still developed is the drone. This research used a drone quadcopter type with 4 propellers synchronized with a configured frame in (X) shape. The previous drone research used google maps and flew autonomously according to the waypoint directed by an android controller application, next, the drone flight command was manual by using a putty application on a laptop. Since, the previous research should be improved, therefore, in this research, the drone used android-based control complete with a tracking feature. Because, android enables the use of computer basic code that can be distributed in open source wit an application tha supports flight controllers along with a tracking application that was a self-designed application using Internet of Things communication (IoT). IoT used in this research is an internet network that can connect electronics and virtual objects around, such as users and types of UAV like a drone. The purpose of maing the drone in this research was to ease tha user in operating and monitoring.